Internalization of Islamic Boarding School Life Values in Forming Multicultural Attitudes of Santri - Abdul Halim (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2023)
Islamic boarding school life, with its culture and learning system, is an educational institution that is unique and different from other institutions. In the context of character education, Islamic boarding schools have an essential role in shaping the attitudes and behaviour of students. The reality of the pluralistic Indonesian nation requires students who can behave multiculturally in society. Meanwhile, Islamic boarding schools, with their deep-rooted values and learning systems, can contribute to forming students' multicultural attitudes. In this study, we discuss Islamic boarding schools' values that play a role in developing the students' multicultural attitudes. These values are the values of honesty, democracy, tolerance, equality, love of the country and respect for cultural diversity. These values form the multicultural attitudes of students by integrating these values into the learning and life of Islamic boarding schools. In the end, values integrated into students' social and education spheres can form a multicultural attitude of students by being tolerant, open, and appreciative of differences and can become role models for students with a multicultural attitude